Zredukuj wyrazy podobne.

a) 100k-{9k-[98k-(97k-k)]}=
b)a+a(do kwadratu)+a(do sześcianu(trzecia potęga))+2a+4a((do sześcianu(trzecia potęga))+7a+5a(do kwadratu)=
c)19e(do kwadratu)-21f-(17f-4f)-(Ee(do kwadratu)-e)=

proszę obliczać dokładnie, a nie zabierać punkty z góry dzięki ;)

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-05T17:43:39+01:00
A)100k-{9k-[98k-(97k-k)]}=100k-{9k-[98k-96k]}=100k-{9k-2k}=100k-7k=93k
b)a+a²+a³+2a+4a³+7a+5a²=10a+6a²+5a³
c)19e²-21f-(17f-4f)-(Ee²-e)=19e²-21f-17f+4f-Ee²+e=19e²-Ee²+e-34f